STEP에 의한 조선 통합 생산 시스템(CIMS) 구현 방법 - 유상봉(S. B. Yoo); 이재원(J. W. Lee); 정용문(Y. M. Jeong); 윤덕영(D. Y. Yoon); 김훈주(H. J. Kim) (大韓造船學會 論文集, 1994)
The role of CIMS(Computer Integrated Manufacturing Systems) is to integrate various applications throughout a product's life cycle. STEP is an international effort to standardize information models and interfaces so that independently developed applications can be easily integrated. A prototype for the Ship CIMS is built using STEP. In this prototype, the information model defined by EXPRESS is translated into database schemas. In this paper, we explain the operation of this prototype using the examples from two application programs, i.e., the Block Division System and the Erection System which are used for the process planning of ship manufacturing. As an example. Real data stored in a relational database system(Oracle) is presented in this paper. 통합 생산 시스템의 역할은 제품의 전 생명주기에 걸쳐 필요한 다수의 응용 프로그램을 통합하는 것이다. STEP은 독립적으로 개발된 응용 프로그램의 통합을 쉽게 하기 위하여 정보모델과 인터페이스를 정의하는 국제 표준화 작업이다. STEP을 이용한 조선 통합생산시스템(CIMS)에서 정보모델은 EXPRESS로 정의되어 있으며, 이 정보모델은 데이타베이스의 스키마로 번역되어 진다. 논문에서는 조선공정계획 시스템에 포함된 두개의 응용 프로그램(즉, 블럭분할 시스템과 탑재 시스템)을 이용하여 개발된 프로토타입의 운용을 설명한다. 예로서 본 논문에서는 관계형 데이타베이스(Oracle)에 저장되어 있는 실제의 데이타를 보여준다.